Real world Adobe Creative Suite 2 - Cohen, Sandee, 1948- (Real world series., 2006)
Adobe's Creative Suite offers a powerful unified design environment that includes Photoshop CS2, Illustrator CS 2, InDesign CS2, GoLive CS2 and Acrobat 7.0. Problem is, you've still got to learn the thing, and learn it well: Your job, after all, depends on it. No one understands that better than the authors of this book, who draw on their own real-world professional knowledge to deliver all the industrial-strength production techniques and timesaving tips you need to start creating print and web projects with the Creative Suite 2 in record time. You'll find everything you need here to successfully master its advanced tools; working with the Adobe Bridge file browser, Stock Photos and more.